1999
DOI: 10.1212/wnl.53.5.1098
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in multiple sclerosis

Abstract: The SF-36 captures the broad effects of MS, and the results showed that patients also are bothered frequently with health problems such as bodily pain and low vitality. These problems, which are not reflected in the Expanded Disability Status Scale, should be given more attention in the treatment of MS and when evaluating interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

27
228
4
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(270 citation statements)
references
References 25 publications
27
228
4
11
Order By: Relevance
“…Furthermore, higher physical disability, disease progression, longer disease duration, and older age were associated with nonemployment (Nortvedt et al, 1999;Grima et al, 2000). Problems related to physical disabilities, concentration deficits and transportation were the most important predictors of adjustment to work among the chronically ill, including neurological diseases (Baanders et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, higher physical disability, disease progression, longer disease duration, and older age were associated with nonemployment (Nortvedt et al, 1999;Grima et al, 2000). Problems related to physical disabilities, concentration deficits and transportation were the most important predictors of adjustment to work among the chronically ill, including neurological diseases (Baanders et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Still, population-based studies show that the majority of patients are ambulatory even after many years of disease duration [1,2]. Health care workers often underestimate the difficulty such MS patients have with work and activities of daily living [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to physical disability, disease-related symptoms such as bladder dysfunction [5], sexual problems [5] and fatigue [6] strongly influence patients' quality of life. Several studies have shown that MS patients have markedly lower quality of life than the general population [1,2,7,8], and also lower than patients with epilepsy, diabetes [9], rheumatoid arthritis and bowel diseases [10]. MS may also influence lifestyles, including such factors as diet, leisure physical activity, smoking and alcohol consumption, which again are known to influence quality of life [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result, the US Food and Drug Administration now mandates the incorporation of HRQOL measures into MS clinical trials. 2 It is postulated that irreversible neuroaxonal loss, which begins in the early stages of MS and is in part independent of new lesion formation, [3][4][5][6][7] may be the primary contributor to disease progression.…”
mentioning
confidence: 99%